OKETANI MASSAGE REDUCES CORTISOL HORMONE LEVELS AMONG BREASTFEEDING MOTHERS IN CITY OF SEMARANG - Machmudah Machmudah; Nikmatul Khayati; Sri Widodo; Hapsari Dwi Elsi; Haryanti Fitri (Fakultas Ilmu Keperawatan Universitas Islam Sultan Agung, Semarang, 2018)
Introduction: A new role of a mother after giving birth is to breastfeed her baby instead of doing other household choirs. This condition will bring stress and tiredness to a mother. Oketani massage not only being useful for increasing breastmilk production but also provide comfort and a feeling of relaxation for the mother. Aim of this study was to describe cortisol levels in breastfeeding mothers who were given oketani massage therapy combine with acupressure at the GB-21 point. Methodology: This research was a quasi experiment with post test design with a control group with a sample of 20 respondents at each group. Statistical analysis using independent T-test. Results: There was a significant difference in the levels of cortisol between control group and oketani massage combine with acupressure group (p = 0.003). Discussion: Oketani massage works well as a pain reliever, providing comfort, relaxation for the post partum mothers. This condition will reduce the level of cortisol hormone and increase blood flow to breasts.